Impact of Inflation on Low-Income Households in Nepal - Adhikari, Aditi; Dahal, Gangadhar (Nepalese Journal of Finance, 2025)
This study analyzed the impact of inflation on low-income households in Nepal. The dependent variable selected for the study is low-income household. Similarly, the selected independent variables are inflation rate, unemployment rate, government policies, exchange rate and price level of essential goods and services. The primary source of data is used to assess the opinions of the respondents regarding low-income household, inflation rate, unemployment rate, government policies, exchange rate and price level of essential goods and services in Nepal. The study is based on primary data of 143 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the impact of low-income households in Nepal. The study showed that inflation rate has positive impact on low-income household. It indicates that inflation rate leads to increase the burden of low-income households. Likewise, unemployment rate has positive impact on low-income household. It indicates that increase in unemployment rate leads to increase the risk of low income households. Furthermore, government policy has positive impact on low-income household. It indicates that f luctuation in government policies leads to increase the risk of low-income households. Likewise, exchange rate has positive impact low-income household. This implies that changes in exchange rates leads to increase the burden of low-income households. Similarly, price level of essential goods and services have positive impact on low-income households. It indicates that higher price levels of essential goods and services, higher will be the burden of low income households.